Validation of a cage implant system for assessing in vivo performance of long-acting release microspheres. (December 2016) - Doty, Amy C.; Hirota, Keiji; Olsen, Karl F.; Sakamoto, Naoya; Ackermann, Rose; Feng, Meihua R.; Wang, Yan; Choi, Stephanie; Qu, Wen; Schwendeman, Anna; Schwendeman, Steven P.
Abstract: Here we describe development of a silicone rubber/stainless steel mesh cage implant system, much like that used to assess biocompatibility of biomaterials [1], for easy removal of injectable polymer microspheres in vivo . The sterile cage has a type 316 stainless steel mesh size (38 μm) large enough for cell penetration and free fluid flow in vivo but small enough for microsphere retention, and a silicone rubber shell for injection of the microspheres. Two model drugs, the poorly soluble steroid, triamcinolone acetonide, and the highly water-soluble luteinizing hormone-releasing hormone (LHRH) peptide superagonist, leuprolide, were encapsulated in PLGA microspheres large enough (63–90 μm) to be restrained by the cage implant in vivo . The in vitro release from both formulations was followed by ultra-performance liquid chromatography (UPLC) with and without the cage in a standard release media, PBS pH 7.4 + 0.02% Tween 80 + 0.05% sodium azide, at 37 °C. Pharmacokinetics (PK) in rats was assessed after SC injection or SC in-cage implantation of microspheres with plasma analysis by LC-MS/MS or EIA. Tr-A and leuprolide in vitro release was largely unaffected after the initial burst irrespective of the cage or test tube incubation vessel and release was much slower than observed in vivo for both drugs. Moreover, Tr-A and leuprolide pharmacokinetics with and without the cage were highly similar during the 2–3 week release duration before a significant inflammatory response was caused by the cage implant. Hence, the PK-validated cage implant provides a simple means to recover and evaluate the microsphere drug carriers in vivo during a time window of at least a few weeks in order to characterize the polymer microsphere release and erosion behavior in vivo . This approach may facilitate development of mechanism-based in vitro/in vivo correlations and enable development of more accurate and useful in vitro release tests.